Preparation and efficacy of antibacterial methacrylate monomer-based polymethyl methacrylate bone cement containing N-halamine compounds - Guo, Rui; Kan, Yu-Chen; Xu, Yang; Han, Lu-Yang; Bu, Wen-Han; Han, Long-Xu; Qi, Yin-Yu; Chu, Jian-Jun (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: Our objective in this study was to prepare a novel type of polymethyl methacrylate (PMMA) bone cement, analyze its material properties, and evaluate its safety and antibacterial efficacy. Methods: A halamine compound methacrylate antibacterial PMMA bone cement containing an N-Cl bond structure was formulated, and its material characterization was determined with Fourier transform infrared spectroscopy (FT-IR) and 1H-NMR. The antibacterial properties of the material were studied using contact bacteriostasis and releasing-type bacteriostasis experiments. Finally, in vitro and in vivo biocompatibility experiments were performed to analyze the toxic effects of the material on mice and embryonic osteoblast precursor cells (MC3T3-E1). Results: Incorporation of the antibacterial methacrylate monomer with the N-halamine compound in the new antibacterial PMMA bone cement significantly increased its contact and releasing-type bacteriostatic performance against Staphylococcus aureus. Notably, at 20% and 25% additions of N-halamine compound, the contact and releasing-type bacteriostasis rates of bone cement samples reached 100% (P < 0.001). Furthermore, the new antibacterial bone cement containing 5%, 10%, and 15% N-halamine compounds showed good biocompatibility in vitro and in vivo. Conclusion: In this study, we found that the novel antibacterial PMMA bone cement with N-halamine compound methacrylate demonstrated good contact and releasing-type bacteriostatic properties against Staphylococcus aureus. In particular, bone cement containing a 15% N-halamine monomer exhibited strong antibacterial properties and good in vitro and in vivo biocompatibility.